Utilization of glucagon-like peptide-1 receptor agonists in children and adolescents in China: a real-world study - Yan, Yilong; Gong, Ying; Jiang, Meizhu; Gao, Yiming; Guo, Shanshan; Huo, Jiping; Zhao, Zhigang; Li, Cao (Frontiers in Endocrinology, 2023)
Background: Glucagon-like peptide-1 receptor agonist (GLP-1RA) has been widely used in treating type 2 diabetes mellitus (T2DM) and obesity in adults, but scientific research about the indication in children and adolescents is scarce. The current study aims to explore the prescriptions of GLP-1RA in children and adolescents in China and to evaluate its rationality. Methods: GLP-1RA prescriptions of children and adolescents were retrospectively obtained from the Hospital Prescription Analysis Cooperative Project. The study extracted information on patient's demographic characteristics, mono-therapy and combination therapy of GLP-1RA, and trends in GLP-1RA usage from 2016 to 2021. The rationality of GLP-1RA prescriptions was comprehensively assessed based on the indications approved by China National Medical Products Administration (NMPA), the U.S. Food and Drug Administration (FDA), and published randomized controlled trials (RCTs). Results: A total of 234 prescriptions from 46 hospitals were included, with a median age of 17 years old. The majority of patients were diagnosed with diabetes/pre-diabetes or obesity/overweight, accounting for 46.15% and 43.59%, respectively. There were 88 patients on GLP-1RA mono-therapy. GLP-1RA plus metformin was the most common combination therapy (38.89%). 12.39% of patients were found a co-administration with orlistat. The share of obesity/overweight prescriptions increased from 27% in 2016 to 54% in 2021, whereas diabetes/pre-diabetes prescriptions declined from 55% to 42%. The prescriptions were divided into appropriate and questionable groups according to the diagnosis, and the potentially questionable prescription was related to age (p = 0.017), department visited (p = 0.002), and any hospitalization (p＜0.001). Conclusions: This study described the prescribing of GLP-1RA in children and adolescents. Our findings indicated that the utilization of GLP-1RA has increased from 2016 to 2021. There was a strong basis for administering GLP-1RA in diabetes/pre-diabetes and obesity, whereas the evidence was insufficient in other conditions. It is crucial to demand robust and sustained efforts to enhance the awareness of the safety of utilization of GLP-1RA in children and adolescents.